Current-Free Electric Double Layer in a Small Collisional Plasma Thruster Nozzle Simulation - Ho, Teck Seng; Charles, Christine; Boswell, Roderick W. (Frontiers in Physics, 2019)
A computational fluid dynamics and plasma model of a collisional (∼ a few Torr) radiofrequency (at 13.56 MHz) argon plasma capacitively coupled in a converging-diverging nozzle (applied to the optimisa- tion of electrothermal plasma thrusters for space use) shows the formation of a strong stationary current-free double layer (CFDL) at the 1.5 mm diameter nozzle throat for a downstream pressure of ∼ 0.1 Torr. The cycle average magnitude of the double layer potential is ∆ΦDL = 77 V and the electron temperature at the high potential edge of the double layer is kBTe = 2.64eV, yielding a strength of ∆ΦDL/(kBTe) ∼ 30. The double layer is 1.2 mm wide which corresponds to ∼ 90 Debye lengths. The axial electric field of the double layer accelerates ions along the nozzle to a maximum drift velocity of 17 km s−1, about 3.3 times the ion sound speed, and their kinetic energy is transferred to neutrals by ion-neutral charge exchange col- lisions. The ion transit time τi through the potential structure spontaneously forming at the nozzle throat is about 5 times the radiofrequency excitation period τRF. These findings are discussed in the broader context of double layer physics and the dynamics of their formation as well as in the context of electrothermal thruster optimisation in which neutral propellant heating via ion-neutral charge exchange collisions is the main source of thrust.